The rancher meets his match - Pearce, Kate, 1963- (Pearce, Kate, 1963- Millers of Morgantown, 2021)
"For the hardworking folks of Morgantown, home really is where the heart is. But sometimes it takes leaving for a while to figure that out... Kaiden Miller may be the family jokester, but he takes his work on their ranch very seriously. And as a sought-after master carpenter to boot, he's busier than ever. Still, when he's asked to renovate the neighboring ranch, he's more than willing. The owner, Juan Garcia, is ailing, and Kaiden expects to find the property pretty run down. He doesn't expect to find his old nemesis--Juan's daughter, Julia--overseeing his work... Julia's not sure why Kaiden never liked her. But if working with him makes life easier for her father, so be it. Yet to her surprise, not only is Kaiden great with her father, he's great with her too. As the weeks pass, it becomes harder to ignore their simmering attraction. And when Julia's boss turns up with a sweet deal, both she and Kaiden will have to decide where their loyalties--and their hearts--lie..."--Provided by publisher.